Melatonin Relieves Ozone Stress in Grape Leaves by Inhibiting Ethylene Biosynthesis - Liu, Chuang; Kang, Hui; Wang, Yafang; Yao, Yuxin; Gao, Zhen; Du, Yuanpeng (Frontiers in Plant Science, 2021)
Ozone (O3) stress severely affects the normal growth of grape (Vitis vinifera L.) leaves. Melatonin (MT) plays a significant role in plant response to various abiotic stresses, but its role in O3 stress and related mechanisms are poorly understood. In order to understand the mechanism of MT in alleviate O3 stress in grape leaves, we perform a transcriptome analyses of grapes leaves under O3 stress with or without MT treatment. Transcriptome analysis showed that the processes of ethylene biosynthesis and signaling were clearly changed in “Cabernet Sauvignon” grapes under O3 and MT treatment. O3 stress induced the expression of genes related to ethylene biosynthesis and signal transduction, while MT treatment significantly inhibited the ethylene response mediated by O3 stress. Further experiments showed that both MT and aminoethoxyvinylglycine (AVG, an inhibitor of ethylene biosynthesis) enhanced the photosynthetic and antioxidant capacities of grape leaves under O3 stress, while ethephon inhibited those capacities. The combined treatment effect of MT and ethylene inhibitor was similar to that of MT alone. Exogenous MT reduced ethylene production in grape leaves under O3 stress, while ethephon and ethylene inhibitors had little effect on the MT content of grape leaves after O3 stress. However, overexpression of VvACO2 (1-aminocyclopropane-1-carboxylate oxidase2) in grape leaves endogenously induced ethylene accumulation and aggravated O3 stress. Overexpression of the MT synthesis gene VvASMT1 (acetylserotonin methyltransferase1) in tobacco (Nicotiana tabacum L.) alleviated O3 stress and reduced ethylene biosynthesis after O3 stress. In summary, MT can alleviate O3 stress in grape leaves by inhibiting ethylene biosynthesis.